Saliva Proteins of Vector Culicoides Modify Structure and Infectivity of Bluetongue Virus Particles - Darpel, Karin E. (Public Library of Science, 2011)
Bluetongue virus (BTV) and epizootic haemorrhagic disease virus (EHDV) are related orbiviruses, transmitted between their ruminant hosts primarily by certain haematophagous midge vectors (Culicoides spp.). The larger of the BTV outer-capsid proteins, ‘VP2’, can be cleaved by proteases (including trypsin or chymotrypsin), forming infectious subviral particles (ISVP) which have enhanced infectivity for adult Culicoides, or KC cells (a cell-line derived from C. sonorensis). We demonstrate that VP2 present on purified virus particles from 3 different BTV strains can also be cleaved by treatment with saliva from adult Culicoides. The saliva proteins from C. sonorensis (a competent BTV vector), cleaved BTV-VP2 more efficiently than those from C. nubeculosus (a less competent / non-vector species). Electrophoresis and mass spectrometry identified a trypsin-like protease in C. sonorensis saliva, which was significantly reduced or absent from C. nubeculosus saliva. Incubating purified BTV-1 with C. sonorensis saliva proteins also increased their infectivity for KC cells ∼10 fold, while infectivity for BHK cells was reduced by 2–6 fold. Treatment of an ‘eastern’ strain of EHDV-2 with saliva proteins of either C. sonorensis or C. nubeculosus cleaved VP2, but a ‘western’ strain of EHDV-2 remained unmodified. These results indicate that temperature, strain of virus and protein composition of Culicoides saliva (particularly its protease content which is dependent upon vector species), can all play a significant role in the efficiency of VP2 cleavage, influencing virus infectivity. Saliva of several other arthropod species has previously been shown to increase transmission, infectivity and virulence of certain arboviruses, by modulating and/or suppressing the mammalian immune response. The findings presented here, however, demonstrate a novel mechanism by which proteases in Culicoides saliva can also directly modify the orbivirus particle structure, leading to increased infectivity specifically for Culicoides cells and, in turn, efficiency of transmission to the insect vector.